2012
DOI: 10.1007/s00404-012-2224-7
|View full text |Cite
|
Sign up to set email alerts
|

Body weight changes after the diagnosis of endometrial cancer and their influences on disease-related prognosis

Abstract: Weight loss after the diagnosis and treatment of cancer may be an adverse prognostic factor. Although it was impossible to distinguish between intentional and non-intentional weight loss, these results argue against weight loss for risk reduction in patients with confirmed endometrial cancer. However, it may be reasonable regarding the risk reduction of non-cancer related morbidity and mortality. Detailed, prospective randomised trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Some evidence indicates that intentional weight loss and prevention of weight cycling may reduce the risk of developing endometrial pathology [26]. However, other studies indicate that weight loss after the diagnosis of endometrial cancer may actually confer a worse prognosis [27]. Counseling at‐risk patients and encouraging diet, exercise, and lifestyle modifications could potentially attenuate the risk of endometrial pathology in addition to the many other obesity‐related comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…Some evidence indicates that intentional weight loss and prevention of weight cycling may reduce the risk of developing endometrial pathology [26]. However, other studies indicate that weight loss after the diagnosis of endometrial cancer may actually confer a worse prognosis [27]. Counseling at‐risk patients and encouraging diet, exercise, and lifestyle modifications could potentially attenuate the risk of endometrial pathology in addition to the many other obesity‐related comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…The consequences of weight loss for cancer survivors is a crucial issue in survivorship research. Observational studies have demonstrated associations between weight loss and increased risk of recurrence and higher all-cause mortality in several large cohorts of breast cancer survivors [ 34 36 ], with similar adverse effects reported in smaller samples of colorectal and endometrial cancer survivors [ 37 , 38 ]. In one study [ 34 ], associations between weight loss and mortality were stratified by weight status, and there was no evidence that weight loss was less harmful in the obese, although like the present study, there was no information on whether or not the weight loss was intentional.…”
Section: Discussionmentioning
confidence: 97%
“…Soliman et al reported that 58% of over 1500 women in an urban population were unaware that obesity increased the risk for endometrial cancer (9). Middle-aged cancer survivors additionally report low physical activity levels (10), and that two-thirds of oncology patients actually gain additional weight after diagnosis (11), demonstrating an opportunity for intervention in this particular patient population.…”
Section: Introductionmentioning
confidence: 99%